Современные проблемы развития и финансирования предприятий туристской сферы - Калафатов, Э.А. (Культура народов Причерноморья, 2014)
В данной научной статье была рассмотрена туристская сфера крымского региона, а так же все смежные сферы. Проведено исследование туристского потенциала крымского региона, выявлены основные проблемы, которые затрудняют развитие туристского потенциала. На основании изученного материала были предложены пути развития туристской отрасли и всех смежных отраслей, которые способны помочь эффективно использовать тот туристский потенциал крымского региона, который есть, и помочь создать более новое мышление в сфере крымского туризма. У даній науковій статті була розглянута туристична сфера кримського регіону, а так само всі суміжні сфери. Проведено дослідження туристичного потенціалу кримського регіону, виявлені основні проблеми, які ускладнюють розвиток туристичного потенціалу. На підставі вивченого матеріалу були запропоновані шляхи розвитку туристичної галузі та всіх суміжних галузей, які здатні допомогти ефективно використовувати той туристичний потенціал кримського регіону, який є, і допомогти створити більш нове мислення у сфері кримського туризму. In this research paper was considered tourist areas of the Crimean region, as well as all related spheres. Currently, tourism is one of the fastest growing service industries. Speaking as one of the most effective catalysts for the socio-economic development, the tourism industry has a stimulating effect on almost all related sectors of the economy. Tourism is an activity that requires a favorable economic environment for the development and attraction of significant financial resources. Therefore, the question of reviewing the financial security of the tourism industry are important in a practical and theoretical level. In the course of the study identified the main problems that hinder the development of tourist potential. These include: - low level of service; - a small number of consumers of tourist services; - a small market share of individual enterprise tourist areas and small volumes of sales of tourist services; - inefficient interaction of businesses, members of the tourist market, etc. One of the important issues that must be addressed to enterprises of tourist areas for full funding is the need to create (attraction) of the consumer. On the basis of the material studied were proposed the development of the tourism industry and all related industries that are able to help effectively use the tourist potential of the Crimean region, which is, and help create a new way of thinking in the Crimean tourism. It is worth noting that by financing in tourism and creating the conditions for its development, it is necessary to carry out a detailed plan balanced, because the increase in the flow of tourists can have a negative effect (rising prices, environmental degradation, seasonality, the growing discontent of the population, etc.), there is in certain regions.